2020
DOI: 10.1002/jgh3.12328
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on symptoms and treatment modalities used and short‐term follow up of achalasia cardia in Indian setting

Abstract: Background: Achalasia cardia is a rare esophageal motor disorder that is frequently diagnosed late. Aim: The aim of this study was to study the symptoms, treatment given, and response to treatment in patients with achalasia cardia in an Indian setting. Materials and methods: This retrospective study included all patients diagnosed with achalasia cardia on high-resolution esophageal manometry, using Chicago Classification v 3.0. On follow up, patients were contacted by telephone, and details of the treatment gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Dysphasia and regurgitation are common in all subtypes; however, limited studies have reported that regurgitation is more frequent in type I (19) but more severe in type II (6). Previous studies indicated that type II patients reported weight loss more frequently than other subtypes (7,20,21). A possible association between weight loss and subtype of achalasia can include a higher catabolic state and different dietary adaptations in type II; however, further research, including investigation of the relationship between inflammatory status and weight loss, is required due to the small sample size.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysphasia and regurgitation are common in all subtypes; however, limited studies have reported that regurgitation is more frequent in type I (19) but more severe in type II (6). Previous studies indicated that type II patients reported weight loss more frequently than other subtypes (7,20,21). A possible association between weight loss and subtype of achalasia can include a higher catabolic state and different dietary adaptations in type II; however, further research, including investigation of the relationship between inflammatory status and weight loss, is required due to the small sample size.…”
Section: Symptomsmentioning
confidence: 99%
“…Differences in several factors among the three subtypes, such as symptoms (6,7), manometric findings (8), and treatment response (9,10) have been reported so far; however, because of the limited number of studies, the differences are still controversial, and some argue that the three subtypes are the same consecutive disorders. Based on manometric and histopathological findings, a hypothetical clinical course in which achalasia progresses from type III to type II and then to type I has been suggested (11).…”
Section: Introductionmentioning
confidence: 99%
“…The usual age of presentation is 25 -60 years [2] . The duration of symptoms before diagnosis varies from 6 months to 5.9 years [3,4] . Almost all patients have solid food dysphagia and the majority of patients complain of liquid dysphagia.…”
Section: Introductionmentioning
confidence: 99%